2017
DOI: 10.4103/ijps.ijps_8_17
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive functional classification of cleft hand: The DAST concept

Abstract: Context:Phenotypic expressions of the congenital cleft hand are variable and might baffle even the experienced as to the choice of surgery. The morphological parameters defining the anomaly dictate not only the functional capacity of the anomalous hand but also the degree of possible surgical restoration. Despite a large number of classifying systems available, none encompass all the relevant issues.Aims:The purpose of this work is to present an all-inclusive and universally acceptable classification of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…According to the DAST functional classification of cleft hand (D = digits missing, A = associated anomalies in the hand, S = site of cleft, T = functional state of the thumb), the patient presented a D-3 (three or more), A-0, S-1 (1 = central), T-4 (4 is hypoplastic) score on the right side and a D-4, A-0, S-1, T-5 (floating thumb or agenesis) score on the left side. This score implied a severe cleft type that would most likely need reconstruction with a vascularized toe transfer on the left ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the DAST functional classification of cleft hand (D = digits missing, A = associated anomalies in the hand, S = site of cleft, T = functional state of the thumb), the patient presented a D-3 (three or more), A-0, S-1 (1 = central), T-4 (4 is hypoplastic) score on the right side and a D-4, A-0, S-1, T-5 (floating thumb or agenesis) score on the left side. This score implied a severe cleft type that would most likely need reconstruction with a vascularized toe transfer on the left ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Buss., et al reported, concomittant preaxial anomalies over %50 significant, also genitourinary problems around %10 [15]. Vogels reported chromosomal unique anomalia with thrombocytopenia monozomi 21 [16], Miıura, Duran., et al rand many author eported genetic disorders with cleft hand [17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…На сегодняшний день известно значительное количество вариантов клинических классификаций SHFM в зависимости от тяжести недоразвития на кисти [7,8].…”
Section: рис 1 схематическое представление различных типов Shfm: а)unclassified
“…Хирургическому лечению расщепления кисти посвящено значительное количество работ[4,7,8]. Однако в основном они описывают различные виды реконструкций у пациентов с расщеплением кисти при сохранности 1-го, 5-го лучей.…”
unclassified
See 1 more Smart Citation